A positive electrode lithium supplement and its preparation method and application
By mixing halogen-based lithium supplement materials that meet certain particle size requirements and iron-based lithium supplement materials, a mixed positive electrode lithium supplement agent is prepared, which solves the problem of irreversible capacity loss caused by the solid electrolyte membrane formed by the lithium-ion battery during the first charging process, and achieves the effect of improving slurry stability and improving charging capacity.
Patent Information
- Application Number
- CN202211687614.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-27
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-12-27
AI Technical Summary
The solid electrolyte membrane formed by existing lithium-ion batteries during the first charging process results in irreversible capacity loss, limiting the application of high-energy materials, and the existing positive electrode lithium supplementation technology cannot simultaneously improve the charging capacity and improve the stability of the slurry.
By mixing halogen-based lithium supplement material that meets certain particle size requirements and iron-based lithium supplement material, a mixed positive electrode lithium supplement agent is prepared. This lithium supplement agent improves the stability of the positive electrode slurry and improves the first week charging capacity of the battery within the set particle size requirements.
This technical method effectively improves the stability of the positive electrode slurry, improves the first week of the battery charging capacity, solves the problem of irreversible capacity loss, and improves the overall performance of the battery.
Smart Images

Figure BDA0004020083510000131 
Figure BDA0004020083510000141
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium replenishment of lithium ion batteries, and relates to a positive electrode lithium replenisher and a preparation method and application thereof. Background Art
[0002] Research on lithium-ion batteries has made great progress, and the specific capacity, cycle stability and rate performance have all been improved, but there are still many problems. Among them, irreversible capacity loss limits the application of many high-energy materials, and most of the irreversible capacity loss comes from the lithium ions consumed in the formation of the solid electrolyte membrane during the first charging process.
[0003] During the first charging process of a lithium-ion battery, the organic solvent in the electrolyte (such as diethyl carbonate DEC, dimethyl carbonate DMC or propylene carbonate PC, etc.) is very easy to reduce and decompose on the surface of the negative electrode after taking away the lithium ions from the positive electrode, and then form a passivation film, called the solid electrolyte interface film, or SEI film. The SEI film can insulate electrons from passing through and allow lithium ions to pass through. It is an electronic insulator, but it is an excellent ion conductor, which can effectively inhibit the further decomposition of the electrolyte, thereby avoiding the formation of a thicker SEI film after the first cycle. The SEI film mainly contains organic components such as RCOOLi, ROLi and ROCO2Li, as well as inorganic components such as Li2CO3, Li2O, LiOH, and LiF. The process of forming these lithium-containing components is irreversible, and therefore, a portion of the Li from the positive electrode will be irreversibly consumed. + , which reduces the Coulombic efficiency of the first cycle and causes the energy and capacity density of lithium-ion batteries to be low.
[0004] Graphite is currently the most widely used negative electrode material for lithium-ion batteries. Its first irreversible capacity loss is about 10%, while some high-capacity negative electrode materials have even higher first irreversible capacity losses. For example, the first irreversible capacity loss of silicon-based negative electrode materials or tin-based negative electrode materials can be as high as 30% or more. In order to solve the problem of first irreversible capacity loss and improve the first coulomb efficiency, lithium replenishment technology has been developed in large quantities. By replenishing lithium, a new lithium source is added to the electrode material to compensate for the loss of active lithium caused by the formation of the SEI film in the first cycle.
[0005] CN 110854382A relates to a positive electrode lithium supplement material, a positive electrode including the positive electrode lithium supplement material and a preparation method thereof. The positive electrode lithium supplement material includes Li2M1O2, Li2M2O3, Li5Fe x M3 1-x O4 or Li6Mn y M4 1-yO4, wherein M1 comprises at least one of Ni, Mn, Cu, Fe, Cr or Mo; wherein M2 comprises at least one of Ni, Mn, Fe, Mo, Zr, Si, Cu, Cr or Ru; wherein M3 comprises at least one of Al, Nb, Co, Mn, Ni, Mo, Ru or Cr; wherein M4 comprises at least one of Ni, Fe, Cu or Ru; wherein 0≤x≤1, 0≤y≤1.
[0006] CN 115347254A discloses a composite positive electrode lithium supplement additive and its preparation method and application. The composite positive electrode lithium supplement additive comprises positive electrode lithium supplement material particles, and a lithium carbonate coating layer is also combined on the surface of the positive electrode lithium supplement material particles, and the lithium carbonate coating layer covers the positive electrode lithium supplement material particles. The composite positive electrode lithium supplement additive is provided with a lithium carbonate coating layer on the surface of the positive electrode lithium supplement material particles, so that the positive electrode lithium supplement material particles are isolated from the outside world, thereby ensuring the stability of the lithium supplement effect of the composite positive electrode lithium supplement additive, and having a synergistic effect with the high-purity positive electrode lithium supplement material particles, giving the composite positive electrode lithium supplement additive excellent processing and storage performance.
[0007] The above technical solutions for positive electrode lithium supplementation have played a certain role, but they cannot improve the slurry stability while increasing the charging capacity of the positive electrode material. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a positive electrode lithium replenisher and a preparation method and application thereof. The present invention obtains a mixed positive electrode lithium replenisher by mixing a halogen-based lithium replenisher material and an iron-based lithium replenisher material that meet certain particle size requirements. Within the set particle size requirement range, the stability of the positive electrode slurry can be improved, and the first-week charging capacity of the battery is increased.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a positive electrode lithium replenisher, wherein the positive electrode lithium replenisher comprises a halogen-based lithium replenisher material and an iron-based lithium replenisher material;
[0011] The particle size of the halogen-based lithium-supplementing material and the particle size of the iron-based lithium-supplementing material independently satisfy:
[0012] 3≤(D90-D10) / D50≤5, for example, it can be 3, 3.5, 4, 4.5 or 5, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0013] The present invention obtains a mixed positive electrode lithium replenisher by mixing a halogen-based lithium replenisher material and an iron-based lithium replenisher material that meet certain particle size requirements. If the particle size is too small, the specific surface area of the lithium replenisher material increases, the contact area with the glue solution increases, and the slurry viscosity rebounds severely in a short time and cannot be used continuously; if the particle size is too large, the slurry becomes uneven during homogenization, and there are too many particles, which cannot be coated or used as a battery. Within the set particle size requirement range, the stability of the positive electrode slurry is improved, and the first-week charging capacity of the battery is increased.
[0014] Preferably, the halogen-based lithium supplement material is Li2OHCl.
[0015] Preferably, the iron-based lithium supplement material is Li5FeO4.
[0016] Preferably, the mass ratio of the halogen-based lithium-replenishing material to the iron-based lithium-replenishing material is (0.2-5):1, for example, it can be 0.2:1, 0.5:1, 1:1, 2:1, 4:1 or 5:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] Preferably, the particle size of the halogen-based lithium-supplementing material and the particle size of the iron-based lithium-supplementing material independently satisfy:
[0018] 3.7≤(D90-D10) / D50≤4.5, for example, it can be 3.7, 3.9, 4, 4.2 or 4.5, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0019] Preferably, the relationship between the specific surface area (SSA) and the particle size of the halogen-based lithium-supplementing material and the relationship between the specific surface area and the particle size of the iron-based lithium-supplementing material independently satisfy:
[0020] 0.24≤SSA / D50≤0.32, for example, it can be 0.24, 0.26, 0.28, 0.3 or 0.32, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0021] Because the particle size is too small, the specific surface area of the lithium replenisher material increases, the contact area with the glue solution increases, and the slurry viscosity rebounds severely in a short time, and it cannot be used anymore; if the particle size is too large, the slurry becomes uneven during homogenization, and there are too many particles to be coated or used as a battery. When the particle size and specific surface area of the halogen-based lithium replenisher material and the iron-based lithium replenisher material in the positive electrode lithium replenisher satisfy the above relationship, the stability of the positive electrode slurry is improved, and the first-week charging capacity of the battery is increased.
[0022] In a second aspect, the present invention provides a method for preparing the positive electrode lithium supplement according to the first aspect, the preparation method comprising the following steps:
[0023] (1) mixing non-halogenated lithium and lithium halide, calcining, crushing and screening to obtain a halogen-based lithium supplement material;
[0024] (2) mixing a lithium source and an iron source, calcining, crushing and screening to obtain an iron-based lithium supplement material;
[0025] (3) mixing the obtained halogen-based lithium replenishing material and the obtained iron-based lithium replenishing material to obtain the positive electrode lithium replenishing agent;
[0026] The order of steps (1) and (2) is not critical.
[0027] Preferably, the non-halide lithium source in step (1) comprises any one of anhydrous lithium hydroxide, lithium hydroxide monohydrate, lithium oxide, lithium bromide or lithium carbonate, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of anhydrous lithium hydroxide and lithium hydroxide monohydrate, a combination of lithium hydroxide monohydrate and lithium oxide, a combination of lithium oxide and lithium bromide, a combination of lithium bromide and lithium carbonate, a combination of anhydrous lithium hydroxide and lithium hydroxide monohydrate and lithium oxide, a combination of lithium hydroxide monohydrate and lithium oxide and lithium bromide, and a combination of lithium oxide and lithium bromide and lithium carbonate.
[0028] Preferably, the lithium halide in step (1) comprises anhydrous lithium chloride.
[0029] Preferably, the non-halide lithium source and the lithium halide in step (1) are each independently subjected to air flow pulverization.
[0030] Preferably, the grinding gas pressure of the air flow milling is 0.1-0.6 MPa, for example, it can be 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa or 0.6 MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, the feeding frequency of the air flow milling is 5 to 15 Hz, for example, 5 Hz, 8 Hz, 10 Hz, 12 Hz or 15 Hz, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0032] Preferably, the molar ratio of the non-halide lithium source and the lithium halide in step (1) is 1 to 1.1, for example, 1, 1.02, 1.05, 1.08 or 1.1, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0033] Preferably, the mixing in step (1) includes stirring, and the stirring speed is 500 to 2000 rpm, for example, it can be 500 rpm, 700 rpm, 1000 rpm, 1500 rpm or 2000 rpm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] Preferably, the stirring time is 0.5 to 5 h, for example, 0.5 h, 1 h, 2 h, 3 h, 4 h or 5 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0035] Preferably, the calcination in step (1) is carried out in a nitrogen atmosphere.
[0036] Preferably, the concentration of the nitrogen is ≥99.99%, for example, it may be 99.99%, 99.999%, 99.9999%, 99.99999% or 100%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0037] Preferably, the flow rate of the nitrogen is 0.5 to 5 L / min, for example, 0.5 L / min, 1 L / min, 2 L / min, 3 L / min, 4 L / min or 5 L / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0038] Preferably, the calcination in step (1) includes heating and keeping warm.
[0039] Preferably, the heating rate is 2 to 10°C / min, for example, 2°C / min, 4°C / min, 6°C / min, 8°C / min or 10°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] Preferably, the insulation temperature is 300-500°C, for example, 300°C, 350°C, 400°C, 450°C or 500°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] Preferably, the insulation time is 0.5 to 10 h, for example, 0.5 h, 2 h, 4 h, 8 h or 10 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0042] Preferably, the mesh size of the sieving in step (1) is 300-400 mesh, for example, 300 mesh, 320 mesh, 350 mesh, 380 mesh or 400 mesh, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0043] Preferably, the lithium source in step (2) comprises any one of anhydrous lithium hydroxide, lithium hydroxide monohydrate, lithium oxide, lithium bromide or lithium carbonate, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of anhydrous lithium hydroxide and lithium hydroxide monohydrate, a combination of lithium hydroxide monohydrate and lithium oxide, a combination of lithium oxide and lithium bromide, a combination of lithium bromide and lithium carbonate, a combination of anhydrous lithium hydroxide and lithium hydroxide monohydrate and lithium oxide, a combination of lithium hydroxide monohydrate and lithium oxide and lithium bromide, and a combination of lithium oxide and lithium bromide and lithium carbonate.
[0044] Preferably, the lithium source in step (2) is subjected to air flow pulverization.
[0045] Preferably, the grinding gas pressure of the air flow milling is 0.1-0.6 MPa, for example, it can be 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa or 0.6 MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] Preferably, the feeding frequency of the air flow milling is 5 to 15 Hz, for example, 5 Hz, 8 Hz, 10 Hz, 12 Hz or 15 Hz, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0047] Preferably, the iron source in step (2) comprises any one of ferric oxide, ferric chloride, ferric nitrate, ferric sulfate or ferric bromide, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of ferric oxide and ferric chloride, a combination of ferric chloride and ferric nitrate, a combination of ferric nitrate and ferric sulfate, a combination of ferric sulfate and ferric bromide, a combination of ferric oxide, ferric chloride and ferric nitrate, a combination of ferric chloride, ferric nitrate and ferric sulfate, a combination of ferric nitrate, ferric sulfate and ferric bromide, a combination of ferric oxide, ferric chloride, ferric nitrate and ferric sulfate, and a combination of ferric chloride, ferric nitrate, ferric sulfate and ferric bromide.
[0048] Preferably, the lithium source and the iron source in step (2) are mixed according to a Li / Fe molar ratio of 1:(5-6), for example, 1:5, 1:5.2, 1:5.5, 1:5.8 or 1:6, but not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0049] Preferably, the mixing speed in step (2) is 500-1000 rpm, for example, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm or 1000 rpm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0050] Preferably, the mixing time in step (2) is 0.5 to 2 h, for example, 0.5 h, 0.8 h, 1 h, 1.5 h or 2 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0051] The calcination in step (2) is carried out in a nitrogen atmosphere.
[0052] Preferably, the concentration of the nitrogen is ≥99.99%, for example, it may be 99.99%, 99.999%, 99.9999%, 99.99999% or 100%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0053] Preferably, the flow rate of the nitrogen is 0.5 to 5 L / min, for example, 0.5 L / min, 1 L / min, 2 L / min, 3 L / min, 4 L / min or 5 L / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0054] Preferably, the calcination in step (2) includes heating and keeping warm.
[0055] Preferably, the heating rate is 2-5°C / min, for example, 2°C / min, 2.5°C / min, 3°C / min, 4°C / min or 5°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] Preferably, the insulation temperature is 500-900°C, for example, 500°C, 600°C, 700°C, 800°C or 900°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] Preferably, the insulation time is 0.5 to 20 hours, for example, 0.5 hours, 1 hour, 5 hours, 10 hours or 20 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0058] As a preferred technical solution of the preparation method described in the second aspect of the present invention, the preparation method comprises the following steps:
[0059] (1) mixing a non-halogenated lithium source and anhydrous lithium chloride in a molar ratio of 1 to 1.1, stirring at a speed of 500 to 2000 rpm for 0.5 to 5 hours, calcining the mixture in a nitrogen atmosphere with a concentration of ≥99.99% and a flow rate of 0.5 to 5 L / min, first heating to 300 to 500° C. at a rate of 2 to 10° C. / min, keeping the temperature for 0.5 to 10 hours, cooling to 50 to 150° C., and then crushing through a 300 to 400 mesh sieve to obtain a halogen-based lithium supplement material;
[0060] (2) mixing a lithium source and an iron source according to a molar ratio of Li / Fe of 1:(5-6), stirring at a speed of 500-1000 rpm for 0.5-2 h, calcining the mixture in a nitrogen atmosphere with a concentration of ≥99.99% and a flow rate of 0.5-5 L / min, first heating to 500-900° C. at a rate of 2-10° C. / min, keeping the temperature for 0.5-20 h, cooling to 50-150° C., and then crushing and sieving to obtain an iron-based lithium supplement material;
[0061] (3) mixing the obtained halogen-based lithium replenishing material and the obtained iron-based lithium replenishing material in a mass ratio of (0.2-5):1 to obtain the positive electrode lithium replenishing agent;
[0062] The non-halogenated lithium source, anhydrous lithium chloride in step (1) and the lithium source in step (2) are each independently subjected to air flow pulverization at a grinding gas pressure of 0.1 to 0.6 MPa and a feeding frequency of 5 to 15 Hz;
[0063] The order of steps (1) and (2) is not critical.
[0064] In the present invention, air flow pulverization is first performed and then mixed preparation is performed, so that large-particle lithium source can be pulverized into small-particle lithium source, the specific surface area is increased, the reaction is easy to proceed, the calcination temperature required for high-temperature solid-phase reaction is reduced, the energy consumption is reduced, and thus the cost is reduced.
[0065] In a third aspect, the present invention provides a positive electrode sheet, wherein the positive electrode sheet contains the positive electrode lithium supplement agent as described in the first aspect.
[0066] Preferably, the positive electrode sheet is obtained by coating the positive electrode slurry on a current collector and then drying it.
[0067] Preferably, the positive electrode slurry comprises a positive electrode material, a conductive agent, a binder and the positive electrode lithium supplement agent as described in the first aspect.
[0068] Preferably, the mass percentage of the positive electrode lithium supplement is 1-3wt%, for example, 1wt%, 1.5wt%, 2wt%, 2.5wt% or 3wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0069] In a fourth aspect, the present invention provides a battery, wherein the battery contains the positive electrode lithium supplement as described in the first aspect or the positive electrode sheet as described in the third aspect.
[0070] Compared with the prior art, the present invention has at least the following beneficial effects:
[0071] The present invention obtains a mixed positive electrode lithium replenishing agent by mixing a halogen-based lithium replenishing material and an iron-based lithium replenishing material that meet certain particle size requirements. Within the set particle size requirement range, the stability of the positive electrode slurry is improved and the first-week charging capacity of the battery is increased. DETAILED DESCRIPTION
[0072] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0073] Example 1
[0074] This embodiment provides a positive electrode lithium replenisher, which includes a halogen-based lithium replenisher material Li2OHCl and an iron-based lithium replenisher material Li5FeO4 in a mass ratio of 2:1.
[0075] The particle size of the halogen-based lithium-replenishing material and the particle size of the iron-based lithium-replenishing material each independently satisfy: (D90-D10) / D50=4.1; the relationship between the specific surface area and particle size of the halogen-based lithium-replenishing material and the relationship between the specific surface area and particle size of the iron-based lithium-replenishing material each independently satisfy: SSA / D50=0.28.
[0076] The preparation method of the positive electrode lithium supplement comprises the following steps:
[0077] (1) Anhydrous lithium hydroxide and anhydrous lithium chloride were mixed in a molar ratio of 1.05:1, and stirred at a speed of 1000 rpm for 2.5 hours. The mixture was calcined in a nitrogen atmosphere with a concentration of ≥99.99% and a flow rate of 2.5 L / min, first heated to 400° C. at a rate of 6° C. / min, kept warm for 5 hours, cooled to 100° C., and then crushed through a 350-mesh sieve to obtain a halogen-based lithium supplement material Li2OHCl;
[0078] (2) Anhydrous lithium hydroxide and ferric oxide were mixed according to a Li / Fe molar ratio of 1:5.5, and stirred at a speed of 800 rpm for 1 hour. The mixture was calcined in a nitrogen atmosphere with a concentration of ≥99.99% and a flow rate of 2.5 L / min, first heated to 800°C at a rate of 6°C / min, kept warm for 10 hours, cooled to 100°C, and then crushed and sieved to obtain the iron-based lithium supplement material Li5FeO4;
[0079] (3) mixing the obtained Li2OHCl and Li5FeO4 in a mass ratio of 2:1 to obtain the positive electrode lithium supplement;
[0080] The anhydrous lithium hydroxide and anhydrous lithium chloride in step (1) and the anhydrous lithium hydroxide in step (2) are each independently subjected to air flow pulverization with a grinding gas pressure of 0.35 MPa and a feeding frequency of 10 Hz.
[0081] Example 2
[0082] This embodiment provides a positive electrode lithium replenisher, which includes a halogen-based lithium replenisher material Li2OHCl and an iron-based lithium replenisher material Li5FeO4 in a mass ratio of 0.2:1.
[0083] The particle size of the halogen-based lithium-replenishing material and the particle size of the iron-based lithium-replenishing material each independently satisfy: (D90-D10) / D50=4.3; the relationship between the specific surface area and particle size of the halogen-based lithium-replenishing material and the relationship between the specific surface area and particle size of the iron-based lithium-replenishing material each independently satisfy: SSA / D50=0.3.
[0084] The preparation method of the positive electrode lithium supplement comprises the following steps:
[0085] (1) mixing lithium carbonate and anhydrous lithium chloride in a molar ratio of 1, stirring at a speed of 500 rpm for 5 h, calcining the mixture in a nitrogen atmosphere with a concentration of ≥99.99% and a flow rate of 0.5 L / min, first heating to 500° C. at a rate of 2° C. / min, keeping the temperature for 0.5 h, cooling to 50° C., and then crushing through a 300-mesh sieve to obtain a halogen-based lithium supplement material;
[0086] (2) lithium carbonate and ferric chloride were mixed in a Li / Fe molar ratio of 1:5, and stirred at a speed of 500 rpm for 2 h, and then the mixture was calcined in a nitrogen atmosphere with a concentration of ≥99.99% and a flow rate of 0.5 L / min, first heated to 900° C. at a rate of 2° C. / min, kept warm for 0.5 h, cooled to 50° C., and then crushed and sieved to obtain an iron-based lithium supplement material;
[0087] (3) mixing the obtained halogen-based lithium replenishing material and the obtained iron-based lithium replenishing material in a mass ratio of 0.2:1 to obtain the positive electrode lithium replenishing agent;
[0088] The lithium carbonate and anhydrous lithium chloride in step (1) and the lithium carbonate in step (2) are each independently subjected to air flow pulverization with a grinding gas pressure of 0.6 MPa and a feeding frequency of 5 Hz.
[0089] Example 3
[0090] This embodiment provides a positive electrode lithium replenisher, which includes a halogen-based lithium replenisher material Li2OHCl and an iron-based lithium replenisher material Li5FeO4 in a mass ratio of 5:1.
[0091] The particle size of the halogen-based lithium-replenishing material and the particle size of the iron-based lithium-replenishing material each independently satisfy: (D90-D10) / D50=3.9; the relationship between the specific surface area and particle size of the halogen-based lithium-replenishing material and the relationship between the specific surface area and particle size of the iron-based lithium-replenishing material each independently satisfy: SSA / D50=0.26.
[0092] The preparation method of the positive electrode lithium supplement comprises the following steps:
[0093] (1) mixing lithium oxide and anhydrous lithium chloride in a molar ratio of 1.1, stirring at a speed of 2000 rpm for 0.5 h, calcining the mixture in a nitrogen atmosphere with a concentration of ≥99.99% and a flow rate of 5 L / min, first heating to 300° C. at a rate of 10° C. / min, keeping the temperature for 10 h, cooling to 150° C., and then crushing through a 400-mesh sieve to obtain a halogen-based lithium supplement material;
[0094] (2) mixing lithium oxide and ferric nitrate according to a Li / Fe molar ratio of 1:6, and stirring at a speed of 1000 rpm for 0.5 h, calcining the mixture in a nitrogen atmosphere with a concentration of ≥99.99% and a flow rate of 5 L / min, first heating to 500° C. at a rate of 10° C. / min, keeping the temperature for 20 h, cooling to 150° C., and then crushing and sieving to obtain an iron-based lithium supplement material;
[0095] (3) mixing the obtained halogen-based lithium replenishing material and the obtained iron-based lithium replenishing material in a mass ratio of 5:1 to obtain the positive electrode lithium replenishing agent;
[0096] The lithium oxide and anhydrous lithium chloride in step (1) and the lithium oxide in step (2) are each independently subjected to air flow pulverization with a grinding gas pressure of 0.1 MPa and a feeding frequency of 15 Hz.
[0097] Example 4
[0098] This embodiment provides a positive electrode lithium replenisher, which is different from the embodiment 1 in that the particle size of the halogen-based lithium replenisher material and the particle size of the iron-based lithium replenisher material each independently satisfy: (D90-D10) / D50=5;
[0099] Correspondingly, the pulverizing parameters in the preparation method are changed to adjust the particle size.
[0100] Example 5
[0101] This embodiment provides a positive electrode lithium replenisher, which is different from the embodiment 1 in that the particle size of the halogen-based lithium replenisher material and the particle size of the iron-based lithium replenisher material each independently satisfy: (D90-D10) / D50=3;
[0102] Correspondingly, the pulverizing parameters in the preparation method are changed to adjust the particle size.
[0103] Example 6
[0104] This embodiment provides a positive electrode lithium supplement, which is different from the embodiment 1 in that the relationship between the specific surface area and particle size of the iron-based lithium supplement material independently satisfies: SSA / D50=0.2;
[0105] Correspondingly, the pulverizing parameters in the preparation method are changed to adjust the particle size and specific surface area.
[0106] Example 7
[0107] This embodiment provides a positive electrode lithium supplement, which is different from the embodiment 1 in that the relationship between the specific surface area and particle size of the halogen-based lithium supplement material and the relationship between the specific surface area and particle size of the iron-based lithium supplement material independently satisfy: SSA / D50=0.35;
[0108] Correspondingly, the pulverizing parameters in the preparation method are changed to adjust the particle size and specific surface area.
[0109] Example 8
[0110] This embodiment provides a positive electrode lithium supplement, which is different from Embodiment 1 in that the non-halide lithium source and anhydrous lithium chloride in step (1) and the lithium source in step (2) are not subjected to airflow pulverization.
[0111] Comparative Example 1
[0112] This comparative example provides a positive electrode lithium replenisher, which is different from Example 1 in that the positive electrode lithium replenisher is only Li2OHCl.
[0113] Comparative Example 2
[0114] This comparative example provides a positive electrode lithium replenisher, which is different from Example 1 in that the positive electrode lithium replenisher is only Li5FeO4.
[0115] Comparative Example 3
[0116] This comparative example provides a positive electrode lithium replenisher, which is different from Example 1 in that the particle size of the halogen-based lithium replenisher and the particle size of the iron-based lithium replenisher each independently satisfy: (D90-D10) / D50=2.5;
[0117] Correspondingly, the pulverizing parameters in the preparation method are changed to adjust the particle size.
[0118] Comparative Example 4
[0119] This comparative example provides a positive electrode lithium replenisher, which is different from Example 1 in that the particle size of the halogen-based lithium replenisher and the particle size of the iron-based lithium replenisher each independently satisfy: (D90-D10) / D50=5.5;
[0120] Correspondingly, the pulverizing parameters in the preparation method are changed to adjust the particle size.
[0121] The positive electrode lithium supplement agent obtained above was mixed with a conductive agent, a binder, oxalic acid, a positive electrode material and NMP, and after being mixed evenly, it was coated, rolled, cut into pieces and assembled into button batteries, and the electrochemical performance was tested. The test results are shown in Table 1. When no lithium supplement material was added, the 0.1C charge and discharge capacities of the positive electrode material were 160.6 mAh / g and 150.3 mAh / g, respectively.
[0122] Table 1
[0123]
[0124]
[0125] The following conclusions can be drawn from Table 1:
[0126] (1) It can be seen from Examples 1-3 and Comparative Examples 1-4 that the present invention obtains a mixed positive electrode lithium replenisher by mixing a halogen-based lithium replenisher material and an iron-based lithium replenisher material that meet certain particle size requirements. Within the set particle size requirement range, the stability of the positive electrode slurry can be improved and the first-week charging capacity of the battery can be increased.
[0127] (2) From the comparison between Examples 4 and 5 and Example 1, it can be seen that when the particle size satisfies 3.7≤(D90-D10) / D50≤4.5, the positive electrode lithium supplement has the best effect on improving the first-week charging capacity of the battery.
[0128] (3) From the comparison between Examples 6 and 7 and Example 1, it can be seen that when the particle size and specific surface area of the halogen-based lithium replenishing material and the iron-based lithium replenishing material in the positive electrode lithium replenishing agent satisfy the relationship of 0.24≤SSA / D50≤0.32, the stability of the positive electrode slurry is improved and the first-week charging capacity of the battery is increased.
[0129] (4) From the comparison between Examples 8 and 9 and Example 1, it can be seen that when the mass ratio of the halogen-based lithium-supplementing material to the iron-based lithium-supplementing material exceeds the preferred range of the present invention, it is not conducive to improving the stability of the positive electrode slurry and affects the first-cycle charging capacity of the battery.
[0130] In summary, the present invention obtains a mixed positive electrode lithium replenisher by mixing a halogen-based lithium replenisher material and an iron-based lithium replenisher material that meet certain particle size requirements. Within the set particle size requirement range, the stability of the positive electrode slurry can be improved and the first-week charging capacity of the battery can be increased.
[0131] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A positive electrode lithium supplement, characterized in that: The positive electrode lithium supplement includes a halogen-based lithium supplement material and an iron-based lithium supplement material; The particle size of the halogen-based lithium-supplementing material and the particle size of the iron-based lithium-supplementing material independently satisfy: 3≤(D90-D10) / D50≤5; The halogen-based lithium supplement material is Li2OHCl; The iron-based lithium supplement material is Li5FeO4.
2. The positive electrode lithium supplement according to claim 1, characterized in that: The mass ratio of the halogen-based lithium-supplementing material to the iron-based lithium-supplementing material is (0.2-5):
1.
3. The positive electrode lithium supplement according to claim 2, characterized in that: The mass ratio of the halogen-based lithium-supplementing material to the iron-based lithium-supplementing material is 2:
1.
4. The positive electrode lithium supplement according to claim 1, characterized in that: The particle size of the halogen-based lithium-supplementing material and the particle size of the iron-based lithium-supplementing material independently satisfy: 3.7≤(D90-D10) / D50≤4.
5.
5. The positive electrode lithium supplement according to claim 1, characterized in that: The relationship between the specific surface area and particle size of the halogen-based lithium-supplementing material and the relationship between the specific surface area and particle size of the iron-based lithium-supplementing material independently satisfy: 0.24≤SSA / D50≤0.
32.
6. A method for preparing the positive electrode lithium supplement according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) mixing a non-halide lithium source and a lithium halide, calcining, crushing and screening to obtain a halogen-based lithium supplement material; (2) mixing a lithium source and an iron source, calcining, crushing and screening to obtain an iron-based lithium supplement material; (3) mixing the obtained halogen-based lithium replenishing material and the obtained iron-based lithium replenishing material to obtain the positive electrode lithium replenishing agent; The order of steps (1) and (2) is not critical.
7. The preparation method according to claim 6, characterized in that: The non-halide lithium source in step (1) includes any one of anhydrous lithium hydroxide, lithium hydroxide monohydrate, lithium oxide or lithium carbonate, or a combination of at least two thereof.
8. The preparation method according to claim 6, characterized in that: The lithium halide in step (1) includes anhydrous lithium chloride.
9. The preparation method according to claim 6, characterized in that: In step (1), the non-halide lithium source and the lithium halide are each independently subjected to air flow pulverization.
10. The preparation method according to claim 9, characterized in that: The grinding gas pressure of the air flow milling is 0.1-0.6 MPa.
11. The preparation method according to claim 9, characterized in that: The feeding frequency of the air flow milling is 5 to 15 Hz.
12. The preparation method according to claim 6, characterized in that: The molar ratio of the non-halide lithium source and the lithium halide mixed in step (1) is 1 to 1.
1.
13. The preparation method according to claim 6, characterized in that: The mixing in step (1) includes stirring, and the stirring speed is 500 to 2000 rpm.
14. The preparation method according to claim 13, characterized in that: The stirring time is 0.5 to 5 hours.
15. The preparation method according to claim 6, characterized in that: The calcination in step (1) is carried out in a nitrogen atmosphere.
16. The preparation method according to claim 15, characterized in that: The concentration of the nitrogen is ≥99.99%.
17. The preparation method according to claim 15, characterized in that: The flow rate of the nitrogen is 0.5-5 L / min.
18. The preparation method according to claim 6, characterized in that: The calcination in step (1) includes heating and heat preservation.
19. The preparation method according to claim 18, characterized in that: The heating rate is 2-10°C / min.
20. The preparation method according to claim 18, characterized in that: The insulation temperature is 300-500°C.
21. The preparation method according to claim 18, characterized in that: The insulation time is 0.5 to 10 hours.
22. The preparation method according to claim 6, characterized in that: The mesh size of the sieving in step (1) is 300 to 400 meshes.
23. The preparation method according to claim 6, characterized in that: The lithium source in step (2) includes any one of anhydrous lithium hydroxide, lithium hydroxide monohydrate, lithium oxide, lithium bromide or lithium carbonate, or a combination of at least two thereof.
24. The preparation method according to claim 6, characterized in that: The lithium source in step (2) is subjected to air flow pulverization.
25. The preparation method according to claim 24, characterized in that: The grinding gas pressure of the air flow milling is 0.1-0.6 MPa.
26. The preparation method according to claim 24, characterized in that: The feeding frequency of the air flow milling is 5 to 15 Hz.
27. The preparation method according to claim 6, characterized in that: The iron source in step (2) includes any one of ferric oxide, ferric chloride, ferric nitrate, ferric sulfate or ferric bromide, or a combination of at least two thereof.
28. The preparation method according to claim 6, characterized in that: In step (2), the lithium source and the iron source are mixed at a molar ratio of Li / Fe of 1:(5-6).
29. The preparation method according to claim 6, characterized in that: The mixing speed in step (2) is 500 to 1000 rpm.
30. The preparation method according to claim 6, characterized in that: The mixing time in step (2) is 0.5 to 2 hours.
31. The preparation method according to claim 6, characterized in that: The calcination in step (2) is carried out in a nitrogen atmosphere.
32. The preparation method according to claim 31, characterized in that: The concentration of the nitrogen is ≥99.99%.
33. The preparation method according to claim 31, characterized in that: The flow rate of the nitrogen is 0.5-5 L / min.
34. The preparation method according to claim 6, characterized in that: The calcination in step (2) includes heating and heat preservation.
35. The preparation method according to claim 34, characterized in that: The heating rate is 2-5°C / min.
36. The preparation method according to claim 34, characterized in that: The insulation temperature is 500-900°C.
37. The preparation method according to claim 34, characterized in that: The insulation time is 0.5 to 20 hours.
38. The preparation method according to claim 6, characterized in that: The preparation method comprises the following steps: (1) mixing a non-halogenated lithium source and anhydrous lithium chloride in a molar ratio of 1 to 1.1, stirring at a speed of 500 to 2000 rpm for 0.5 to 5 hours, calcining the mixture in a nitrogen atmosphere with a concentration of ≥99.99% and a flow rate of 0.5 to 5 L / min, first heating to 300 to 500° C. at a rate of 2 to 10° C. / min, keeping the temperature for 0.5 to 10 hours, cooling to 50 to 150° C., and then crushing through a 300 to 400 mesh sieve to obtain a halogen-based lithium supplement material; (2) mixing a lithium source and an iron source according to a molar ratio of Li / Fe of 1:(5-6), stirring at a speed of 500-1000 rpm for 0.5-2 h, calcining the mixture in a nitrogen atmosphere with a concentration of ≥99.99% and a flow rate of 0.5-5 L / min, first heating to 500-900° C. at a rate of 2-10° C. / min, keeping the temperature for 0.5-20 h, cooling to 50-150° C., and then crushing and sieving to obtain an iron-based lithium supplement material; (3) mixing the obtained halogen-based lithium replenishing material and the obtained iron-based lithium replenishing material in a mass ratio of (0.2-5):1 to obtain the positive electrode lithium replenishing agent; The non-halogenated lithium source, anhydrous lithium chloride in step (1) and the lithium source in step (2) are each independently subjected to air flow pulverization at a grinding gas pressure of 0.1 to 0.6 MPa and a feeding frequency of 5 to 15 Hz; The order of steps (1) and (2) is not critical.
39. A positive electrode sheet, characterized in that: The positive electrode sheet contains the positive electrode lithium supplement agent according to any one of claims 1 to 5.
40. The positive electrode sheet according to claim 39, characterized in that: The positive electrode sheet is obtained by coating the positive electrode slurry on the current collector and then drying it.
41. The positive electrode sheet according to claim 40, characterized in that: The positive electrode slurry comprises a positive electrode material, a conductive agent, a binder and the positive electrode lithium supplement agent according to any one of claims 1 to 5.
42. The positive electrode sheet according to claim 39, characterized in that: The mass percentage of the positive electrode lithium supplement agent is 1-3wt%.
43. A battery, characterized in that: The battery contains the positive electrode lithium supplement as described in any one of claims 1 to 5 or the positive electrode sheet as described in any one of claims 39 to 42.
Citation Information
Patent Citations
Positive electrode lithium supplement material, positive electrode containing positive electrode lithium supplement material, and preparation method thereof
CN110854382A
Composite positive electrode lithium supplement additive and preparation method and application thereof
CN115347254A
Preparation method and application of small-particle-size lithium supplementing additive Li5FeO4
CN112028126A
Composite positive electrode lithium supplement additive and preparation method and application thereof
CN113471554A